Pendekatan Pendidikan Orang Rimbo Dan Masyarakat Sekitar Guna Mendukung Pariwisata Budaya Adat - Sri Walyoto (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
This study aims to determine the response of Rimbo people and the surrounding community about the establishment of Bukit Duabelas National Park. The study also estimates the value of tourism and culture among domestic tourists to the object using the Travel Cost Method (TCM). The results obtained by consumer surplus (CS) as much as US 2.45 per visitor per visit. The result of CS value of each visitor shows the tourism services in the region does not provide high benefits to tourists. Bukit Duabelas National Park can be a domestic and international eco-cultural tourism destination and welfare improvement. It takes education awareness of tourism and traditional culture of Rimbo people and the surrounding community to achieve it.